Analisis Penggunaan Memrise sebagai Media Pembelajaran Kosakata Bahasa Arab melalui Pendekatan Andragogi - Hanny Khairunisa Qatrunada; Maman Abdurrahman; Nalahuddin Saleh (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study presents analysis by the increasing interest of adults in learning Arabic, but they still face various obstacles such as limited time, low motivation to learn, and limited access to flexible learning media. This study aims to analyze the use of the Memrise application as a medium for learning Arabic vocabulary using an andragogical approach. The approach used is descriptive qualitative, with data collection through observation, semi-structured interviews, and documentation. The research subjects were adult beginners who have never studied Arabic and have used the Memrise app for 14 days. Data analysis was conducted using the Miles and Huberman model, including data reduction, data presentation, and drawing conclusions. The results of the study indicate that Memrise is effective for adult learners because it supports independent, flexible, and adaptive learning processes. Features such as native speaker audio, spaced repetition, and gamification help with vocabulary retention and learning motivation. User score documentation shows consistent daily improvement, reflecting the success of independent and continuous learning. Furthermore, the vocabulary material presented is relevant to the context of learners' daily lives, thereby accelerating the process of internalizing meaning. Despite the limitations of the free version's features, learners can still maximize the learning process. This study concludes that Memrise is a relevant digital learning medium for adult learners in mastering Arabic vocabulary in a practical and sustainable manner.